LA UNIDAD DEL SENTIDO DE LA REALIDAD HISTÓRICA Y SU DIMENSIÓN POLÍTICA EN IGNACIO ELLACURÍA. - Vilches, Daniel; Zuchel, Lorena (Andamios)
In this paper we propose a reading of the philosophical thought of Ignacio Ellacuría, from the Zubirian influence and the diagnosis made by this author of the dehumanizing condition that affected the popular majorities in El Salvador. Firstly, under the scope of some fundamental characterizations about its notion of historical reality, based on the Zubirian anthropological conception. Secondly, we will argue in favor of the realization of the sense of this reality in the process of humanization. And lastly, we will propose the minimum conditions for the politicization of this historical reality based on the process of humanization in the thought of Ignacio Ellacuría.